Side hustle ebook From idea to income in 27 days. - Guillebeau, Chris (2017)
The author of the New York Times Bestseller THE $100 STARTUP, shows how to launch a profitable side hustle in just 27 days.   To some, the idea of quitting their day job to start a business is exhilarating. For others, it’s terrifying. After all, a job that produces a steady paycheck can be difficult to give up.   But in a time when businesses have so little loyalty to employees that the very notion of “job security” has become a punchline, wouldn’t it be great to have an additional source of income to fall back on? And wouldn’t it be great to make that happen  without  leaving your day job?   Enter the Side Hustle. Based on detailed information from hundreds of case studies, Chris Guillebeau provides a step-by-step guide that anyone can use to create and launch a profitable project in less than a month. Designed for the busy and impatient, this plan will have you generating income immediately, without the risk of throwing yourself head first into the world of entrepreneurship.     Whether you just want to make some extra money, or start something that may end up replacing your day job entirely, the side hustle is the new job security. When you generate income from multiple sources, it gives you options, and in today’s world, options aren't just nice to have: they're essential.    You don’t need entrepreneurial experience to launch a profitable side hustle. You don’t need a business degree, know how to code, or be an expert marketer. And you certainly don’t need employees or investors. With this book as your guide, anyone can learn to build a fast track to freedom.